2018
DOI: 10.4187/respcare.06221
|View full text |Cite
|
Sign up to set email alerts
|

Using Objective Fluid Balance Data to Identify Pulmonary Edema in Subjects With Ventilator-Associated Events

Abstract: These findings provide epidemiological evidence of VAEs in a medical ICU and showed that fluid balance may be used to identify pulmonary edema-associated VAEs. Further studies are warranted to validate and translate these findings into an automated surveillance system for VAEs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The VAE rates varied significantly in previous studies, mainly because the denominator used to calculate VAE rate differed among individual studies. For instance, some studies only recruited patients with at least 48 h (7-40.8 per 1000 ventilator-days) [1,2,19,25,27,30,31,38], 4 days (6-13.8 per 1000 ventilator-days) [21,22,24,27,35] or 5 days (107 per 1000 ventilator-days) [4] on a ventilator, while some studies included all mechanically ventilated patients (6.3-14.4 per 1000 ventilator-days) [7,17,23,26,28,33,34,36]. The rates of VAC-plus in our study were slightly higher than in studies with the same VAE definition and all MV episodes as the denominator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The VAE rates varied significantly in previous studies, mainly because the denominator used to calculate VAE rate differed among individual studies. For instance, some studies only recruited patients with at least 48 h (7-40.8 per 1000 ventilator-days) [1,2,19,25,27,30,31,38], 4 days (6-13.8 per 1000 ventilator-days) [21,22,24,27,35] or 5 days (107 per 1000 ventilator-days) [4] on a ventilator, while some studies included all mechanically ventilated patients (6.3-14.4 per 1000 ventilator-days) [7,17,23,26,28,33,34,36]. The rates of VAC-plus in our study were slightly higher than in studies with the same VAE definition and all MV episodes as the denominator.…”
Section: Discussionmentioning
confidence: 99%
“…Several published studies have reported the incidence of VAE. However, the rates varied markedly, ranging from 3 to 77% (6-107 per 1000 ventilator-days) [1,2,4,7,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Explanations for the discrepancy may be various study settings and different patient populations used as the denominator for the calculation of VAE rate.…”
Section: Introductionmentioning
confidence: 99%
“…"-Cardiac ICU attending #1 "In a patient that's having trouble weaning and they don't have a clear reason, after we have treated the pulmonary edema then I will treat for VAT. "-Surgical ICU #3 participants commented on the lack of specificity of those radiographic findings, 14,19 stating that 1 or more clinical symptoms in an actively decompensating patient was sufficient to send respiratory cultures even in the absence of radiographic changes. When discussing respiratory culture reporting, participants stated that when individual organism species are identified, they lean toward VAP diagnosis and completing treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The last update of the new algorithm solved this problem adding a new concept in the algorithm: the IVAC-plus events, that encompasses the other two tiers of the algorithm, IVAC + PVAP. Lately, some authors emphasize the first two tiers as "VAC only/alone" or "IVAC only/alone" when talking about VAEs subtypes to avoid misinterpretations Nakahashi et al, 2018) but other authors can still lead to misunderstanding using the term "IVAC only" meaning IVAC but again using the term IVAC meaning IVAC-plus (Chao et al, 2018).…”
Section: Considerations When Reviewing Vae Research In the Literaturementioning
confidence: 99%